Authentic assessment in optics and photonics - Wong, Nicholas H. L. (Seventeenth Conference on Education and Training in Optics and Photonics: ETOP 2023, 2023)
Schools and universities primarily prepare graduates for the workforce. Conventional pen-and-paper-tests which include multiple choice or theoretical derivations are mainstays in the assessments in most STEM subjects. Practical laboratory tasks, many of which involve carrying out experiments, are also prevalent as assessment components. However, to what degree do these types of assessments test student competency in an applied context? That is, how authentic are these activities in assessing would-be workforce-ready graduates? Authentic assessment focuses on activities that reflect, as accurately as possible, the tasks and contextual environments that employees would typically carry out and be exposed to in a real-world setting. We review developments in authentic assessment and how it can be applied in general STEM as well as specifically optics and photonics contexts.